Ionic Equilibria in Tri-Bivalent Salts (Indium Alum) at 15oC - Mahaseth , Awadhesh; Jha, S.N.; Jha, S.K. (Asian Journal of Chemistry, 2010)
We have measured the dissociation constants of In(SO4)–2 and InSO+4 at 15ºC by E.M.F. method taking [In2(SO4)3]T : [H2SO4]T : 1 : 1. Our values are of the same order as those of Jha and Prasad, who had taken [In2(SO4)3]T : [H2SO4]T : : 4 : 5. The method of computation of result has been improved.